Effect of Dactylaria higginsii on interference of Cyperus rotundus with L. esculentum - Kadir, J.B.; Charudattan, R.; Stall, W.M.; Bewick, T.A. (Weed Science Society of America, 1999)
Greenhouse experiments were conducted to evaluate the effect of the fungus Dactylaria higginsii on the interference of Cyperus rotundus (purple nutsedge) with Lycopersicon esculentum (tomato 'Agroset'). Cyperus rotundus plants established from tubers were planted at initial densities equivalent to 40, 80, 160, and 320 tubers m-2 with L. esculentum in 35-cm-diam pots. Cyperus rotundus plants were inoculated by spraying with a spore suspension of D. higginsii containing 0.5% Metamucil as a carrier. The treatments were Metamucil only, 104 conidia ml-1 + Metamucil, or 106 conidia ml-1 + Metamucil. In the absence of D. higginsii, C. rotundus at densities of 80, 160, and 320 tubers m-2 reduced L. esculentum yield by 14, 68, and 70%, respectively. In contrast, yield of L. esculentum treated with D. higginsii at 106 conidia ml-1 was equal to that in the weed-free control. The rate of disease increase (r(G)) was higher in treatments with 106 conidia ml-1 (r(G) = 0.126 to 0.136) compared to 104 conidia ml-1 (r(G) = 0.046 to 0.050). At 106 conidia ml-1, D. higginsii reduced the interference from C. rotundus, controlled C. rotundus better, and increased L. esculentum yield compared to the weedy checks.